Environment-friendly foaming mortar for wall material and preparation process of environment-friendly foaming mortar

By using modified composite active fillers and polymer powder in cement-based foaming mortar, the problems of degraded mechanical properties and poor freezing resistance in northern regions in winter are solved, and excellent thermal insulation and freezing resistance are achieved.

CN119504209AActive Publication Date: 2025-02-25GUANGDONG DONGKAI NEW MATERIAL TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411573668.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-25
Estimated Expiration
2044-11-05

Smart Images

  • Figure BDA0005121212330000131
    Figure BDA0005121212330000131
Patent Text Reader

Abstract

The invention belongs to the technical field of foaming mortar, and particularly relates to environment-friendly foaming mortar for a wall material and a preparation process of the environment-friendly foaming mortar. The environment-friendly foaming mortar is prepared from the following components in parts by weight: 100 to 200 parts of cement, 40 to 90 parts of modified composite active filler, 0.1 to 0.8 part of sodium carboxymethyl cellulose, 30 to 50 parts of high-molecular polymer powder, 5 to 30 parts of quartz sand, 1 to 5 parts of coagulant, 0.5 to 2 parts of water reducing agent, 3 to 10 parts of foaming agent and 80 to 150 parts of water, the preparation process of the modified composite active filler comprises the following steps: (1) dispersing tetrabutyl orthosilicate, an active filler and a reinforcing filler in water, adding hexadecyl trimethyl ammonium bromide and ammonium bicarbonate, mixing, adjusting the pH value to 10-12 by using ammonia water, and reacting for 24-32 hours in a closed manner at 120-150 DEG C to obtain a mixed material; and (2) filtering, solid-phase drying and roasting the mixed material in sequence to obtain the modified composite active filler.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of foamed mortar, and particularly relates to an environmentally friendly foamed mortar for wall materials and a preparation process thereof. Background Art

[0002] Foamed mortar for walls is a lightweight material that is made by adding a foaming agent to ordinary mortar to form a mixture containing a large number of tiny bubbles. This material is easy to operate during construction and can fill the gaps in the wall, improving the integrity and stability of the structure. When using foamed mortar, make sure to mix it in the correct proportion and method, and follow the relevant construction specifications to ensure the final construction quality and effect.

[0003] Foamed mortars are mainly divided into: (1) cement-based foamed mortar, which has good durability and stability, high compressive strength, but has a large density and heavy weight, and requires more support structures during construction; (2) polymer-based foamed mortar, which has the advantages of light weight and good thermal insulation performance, but has relatively low durability and lower compressive strength than cement-based foamed mortar, and may require an additional protective layer; (3) gypsum-based foamed mortar, which has the advantages of good fire resistance, fast construction speed, smooth surface, and easy decoration, but has poor water resistance, is not suitable for humid environments, and has relatively low strength; (4) fly ash-based foamed mortar, which has the advantages of environmental protection and energy saving, low cost, and certain thermal insulation performance, but its strength and durability are not as good as traditional materials, and it needs to be mixed with other materials to improve its performance; (5) fiber-reinforced foamed mortar, which has excellent crack resistance and impact resistance, but has the disadvantages of relatively high cost, strict construction process requirements, and the need for professional operation. At present, the most researched foam mortar for wall application is cement-based foam mortar. Fly ash and fiber materials are often added to cement-based foam mortar to increase the mechanical properties and thermal insulation of cement-based foam mortar products. However, the thermal insulation effect is not particularly ideal. More importantly, when this type of cement-based foam mortar product is used in winter, especially in northern regions, its mechanical properties decrease significantly, that is, the foam mortar has poor anti-freeze performance, which limits its application.

[0004] Therefore, there is an urgent need for an environmentally friendly foamed mortar for wall materials with excellent thermal insulation, mechanical properties and frost resistance and a preparation process thereof. Summary of the invention

[0005] The purpose of the present invention is to provide an environmentally friendly foamed mortar for wall materials and a preparation process thereof, which has excellent thermal insulation performance, mechanical properties and frost resistance.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides an environmentally friendly foamed mortar for wall materials, which comprises, by weight, 100-200 parts of cement, 40-90 parts of modified composite active filler, 0.1-0.8 parts of sodium carboxymethyl cellulose, 30-50 parts of high molecular polymer powder, 5-30 parts of quartz sand, 1-5 parts of accelerator, 0.5-2 parts of water reducer, 3-10 parts of foaming agent, and 80-150 parts of water; wherein the preparation process of the modified composite active filler comprises: step (1) dispersing butyl orthosilicate, active filler and reinforcing filler in water, adding hexadecyltrimethylammonium bromide and ammonium bicarbonate to mix, then adjusting the pH to 10-12 with ammonia water, and then reacting in a closed state at 120-150° C. for 24-32 hours to obtain a mixture; and step (2) filtering, solid phase drying, and roasting the mixture in sequence to obtain the modified composite active filler.

[0008] The use of modified composite active fillers in the present invention can not only increase the thermal insulation and heat preservation of mortar products to a certain extent, but more surprisingly, it is particularly effective in increasing the frost resistance of mortar products. It is speculated that this is because ammonium bicarbonate is used as a pore-forming agent in the present invention, which can make the modified composite active filler obtained after the closed reaction and calcination of butyl orthosilicate in hexadecyltrimethylammonium bromide and alkaline conditions have special pores, and the mortar slurry can fully wrap the gas generated by the foaming agent. At the same time, its special pore structure can slow down the aggregation and disproportionation of bubbles, thereby preventing gas transfer and physical drainage between gas and liquid phases, thereby improving the workability and fluidity of the slurry. The reinforcing filler in the modified composite active filler can cut off the capillary passage in a freezing environment and reduce the capillary action. At the same time, the micropores of the modified composite active filler and the micropores generated by the specific system of the present invention during the foaming process can release the ice crystal expansion stress in the capillary during the freezing process, further improving the frost resistance. In addition, when butyl orthosilicate is replaced by aluminum hydroxide in the present invention, the strength of the final material is worse than that of butyl orthosilicate. This may be because butyl orthosilicate eventually forms a composite of silicon oxide and active filler, and the silicon dioxide surface has more active bonds, which can better promote the production of gel and finally form a network structure with the modified composite active filler as the core, thereby promoting the overall strength of the material.

[0009] In order to make the various components work better together to increase the overall performance of the foamed mortar products, the environmentally friendly foamed mortar comprises, by weight: 140-165 parts of cement, 60-70 parts of modified composite active filler, 0.3-0.4 parts of sodium carboxymethyl cellulose, 35-40 parts of high molecular polymer powder, 15-20 parts of quartz sand, 2-3 parts of accelerator, 0.8-1 parts of water reducer, 5-7 parts of foaming agent and 100-120 parts of water.

[0010] Furthermore, in step (1), the weight ratio of butyl orthosilicate to hexadecyltrimethylammonium bromide is (10-30):1, for example, 10:1, 12:1, 15:1, 18:1, 20:1, 21:1, 22:1, 23:1, 24:1, 25:1, 27:1, 29:1, 30:1, etc., preferably (20-25:1).

[0011] Furthermore, in step (1), the weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:(0.5-2), for example, 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, etc., preferably 1:(0.8-1.2).

[0012] In the present invention, it is found through experimental research that too much or too little ammonium bicarbonate will affect the performance of the final product. This is because, when the amount of ammonium bicarbonate is too much, the surface pore size of the modified composite active filler is too large, and it is not possible to effectively prevent gas transfer and physical drainage between the gas and liquid phases. When the amount is too little, the surface pore size of the modified composite active filler is too small and uneven, and it is not possible to fully wrap the gas generated by the foaming agent, affecting the workability and fluidity of the slurry, and hindering the micropores generated in the foaming process from releasing the ice crystal expansion stress in the capillary during the freezing process.

[0013] Furthermore, in step (1), the weight ratio of the butyl orthosilicate to the active filler is 1:(1-5), for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:5, etc., preferably 1:(1.5-2).

[0014] Furthermore, in step (1), the weight ratio of the reinforcing filler to the active filler is 1:(0.6-2), preferably 1:(0.8-1.2).

[0015] Furthermore, in step (1), the weight ratio of the active filler to water is (20-40):100, preferably (25-30):100.

[0016] The ammonia water used in the present invention is conventional ammonia water in the art, and its nitrogen content is generally 25-28 wt %.

[0017] The drying conditions in step (2) of the present invention are not particularly limited, as long as the water can be removed. Furthermore, the drying conditions are: drying at 100-120° C. for 2-10 hours.

[0018] Furthermore, the calcination conditions are: calcination at 550-650° C. for 3-5 hours.

[0019] The active filler is fly ash.

[0020] The fly ash may be industrial waste fly ash known to those skilled in the art, and preferably the fly ash is fly ash that meets the secondary standard or above in GB / T 1596.

[0021] Furthermore, the reinforcing filler is a combination of hydrotalcite and oxide whiskers.

[0022] Furthermore, the weight ratio of the hydrotalcite to the oxide whisker is 1:(1-4), preferably 1:(2.5-2.8).

[0023] Furthermore, the average particle size of the hydrotalcite is 0.1-5 microns, preferably 0.3-1 microns, and more preferably 0.6 microns.

[0024] The hydrotalcite in the present invention can be obtained from commercial sources, such as the hydrotalcite of Kaisma, model number: 1-C, the average particle size of which is 0.6 μm.

[0025] Furthermore, the oxide whiskers are selected from Al2O3 whiskers, TiO2 whiskers and MgO whiskers, preferably Al2O3 whiskers.

[0026] Furthermore, the average particle size of the oxide whiskers is 1800-2600 mesh, preferably 2000 mesh.

[0027] The Al2O3 whiskers in the present invention can be obtained commercially, for example, Al2O3 whiskers purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average particle size of 2000 meshes.

[0028] In the present invention, fly ash is a byproduct of coal-fired power plants and is a fine glassy particle with certain volcanic ash activity. Fly ash can increase the fluidity of concrete, making it easier to mix and pour. At the same time, the active ingredients in the fly ash react with the calcium components in cement during the cement hydration process to generate additional hydrated calcium silicate, thereby improving the long-term strength of the concrete. Studies have found that although hydrotalcite and oxide whiskers cannot be used as active fillers alone, the modified composite active filler obtained by composite modification with the active filler fly ash can better increase the strength of the foamed mortar. It is speculated that this is because the oxide whiskers themselves have high tensile strength and thermal shock resistance, and the hydrotalcite has a special layered structure. The two in the system enable the system to form an excellent force dispersion network structure in the gel process, thereby improving the resilience of the material.

[0029] The hydration product formed after cement hydration can provide the strength of the foamed concrete. During the hardening process, it can fill the gaps between aggregates to form a dense microstructure. Furthermore, the cement is selected from at least one of ordinary Portland cement, sulphoaluminate cement, composite Portland cement, ferroaluminate cement and high-alumina refractory cement, preferably ordinary Portland cement. In the present invention, 52.5 grade ordinary Portland cement is used as an exemplary illustration.

[0030] The sodium carboxymethylcellulose in the present invention can be obtained from commercial products, for example, Asahi Kasei cross-linked sodium carboxymethylcellulose ND-2HS.

[0031] Furthermore, the high molecular polymer powder is selected from at least one of polyarylsulfone, tetrafluoroethylene-hexafluoropropylene copolymer, polytetrafluoroethylene, polyimide and polyphenylene sulfide.

[0032] In the present invention, the addition of high molecular polymer powder reduces the amount of cement and other inorganic fillers in the components, thereby making the mortar have a lower density.

[0033] Furthermore, the average particle size of the high molecular polymer powder is 15-50 microns.

[0034] Furthermore, the high molecular polymer powder is selected from tetrafluoroethylene-hexafluoropropylene copolymer and / or polytetrafluoroethylene, preferably tetrafluoroethylene-hexafluoropropylene copolymer.

[0035] The tetrafluoroethylene-hexafluoropropylene copolymer in the present invention can be obtained from the market, for example, the tetrafluoroethylene-hexafluoropropylene copolymer of the brand 6322PZ of 3M of the United States, and its average particle size is 25.6 microns.

[0036] The polytetrafluoroethylene in the present invention can be obtained from the market, for example, polytetrafluoroethylene with the brand number of F-131 of Japan Daikin, which has an average particle size of 19.7 microns.

[0037] In the present invention, the inventors have found that the use of tetrafluoroethylene-hexafluoropropylene copolymer and / or polytetrafluoroethylene, especially tetrafluoroethylene-hexafluoropropylene copolymer can further increase the thermal insulation properties of the material. This may be because the unique chain structure of tetrafluoroethylene-hexafluoropropylene copolymer in the system can increase the degree of entanglement of the system during the hydration-gel process, and can further improve the skeleton structure, pore structure and / or density of the system, while increasing the elongation of the system and reducing the flow of air in the system, thereby better improving the thermal insulation effect of the material.

[0038] Furthermore, the average particle size of the quartz sand is 100-150 meshes.

[0039] The coagulant in the foamed concrete is a chemical additive used to accelerate the solidification and hardening process of the concrete. In the production of foamed concrete, the coagulant can shorten the setting time and improve the early strength, thereby accelerating the construction progress and improving the work efficiency. Further, the coagulant is selected from at least one of gypsum powder, lithium carbonate, sodium silicate, aluminum sulfate, sodium nitrate, calcium nitrate, sodium sulfate and sodium carbonate, preferably a combination of gypsum powder and aluminum sulfate, and the weight ratio of the gypsum powder to aluminum sulfate is 1: (0.5-2), preferably 1: (0.8-1.2).

[0040] The water reducer in foamed concrete is a chemical additive that can reduce the amount of water. The water reducer reduces the friction and surface tension between cement particles, so that cement particles are better dispersed, thereby reducing the amount of water used. The water reducer can improve its fluidity, reduce porosity, improve uniformity and stability, and ultimately achieve the purpose of reducing density, reducing weight, and enhancing thermal insulation performance. Further, the water reducer is selected from at least one of a naphthalene-based water reducer, an aliphatic water reducer, and a polycarboxylic acid-based water reducer, preferably a polycarboxylic acid-based water reducer.

[0041] The water reducing agent used in the present invention is specifically ST-02A polycarboxylic acid-based high-performance water reducing agent.

[0042] Furthermore, the foaming agent is hydrogen peroxide.

[0043] In a second aspect, the present invention provides a preparation process of the environmentally friendly foamed mortar for wall materials according to the first aspect of the present invention, the preparation process comprising:

[0044] S1: mixing cement, modified composite active filler, sodium carboxymethyl cellulose, high molecular polymer powder and quartz sand to obtain a dry mix;

[0045] S2 adds a coagulant, a water reducing agent and water to the dry mix to obtain a mixed material;

[0046] S3 adds a foaming agent into the mixed material and stirs for 2-10 seconds to obtain an environmentally friendly foamed mortar for wall materials.

[0047] In the present invention, the wall material can be poured into a pre-prepared mold using environmentally friendly foamed mortar as required, and then the mold is placed in a suitable environment for curing.

[0048] The foaming agent in step S3 of the present invention can be added when the environmentally friendly foamed mortar for wall materials is needed to prepare the corresponding environmentally friendly foamed mortar for wall materials.

[0049] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0050] 1. In the present invention, polymer powder is used to replace part of the filler, which not only makes the mortar have a lower density, but also the interaction between the polymer powder and other components makes the mortar have excellent thermal insulation performance.

[0051] 2. The modified composite active filler of the present invention contains fly ash, which is generally derived from industrial waste residues, which can reduce resource consumption and environmental pollution and improve the sustainability of the project. At the same time, the modified composite active filler of the present invention interacts with other components to make the mortar not only have excellent strength, but also have excellent cyclic frost resistance. DETAILED DESCRIPTION

[0052] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Example 1

[0054] The present embodiment provides an environmentally friendly foamed mortar for wall materials, which includes, by weight, 155 parts of cement, 68 parts of modified composite active filler, 0.38 parts of sodium carboxymethyl cellulose, 38 parts of high molecular polymer powder, 16 parts of quartz sand, 2.5 parts of accelerator, 0.8 parts of water reducer, 6 parts of foaming agent, and 112 parts of water;

[0055] The preparation process of the modified composite active filler comprises: step (1) dispersing butyl orthosilicate, active filler and reinforcing filler in water, adding hexadecyltrimethylammonium bromide and ammonium bicarbonate to mix, then adjusting the pH value to 11.8 with ammonia water (nitrogen content is 26wt%), and finally reacting at 125°C for 30 hours to obtain a mixture; step (2) filtering, solid phase drying and roasting the mixture in sequence to obtain a modified composite active filler; in step (1), the weight ratio of butyl orthosilicate to hexadecyltrimethylammonium bromide is 23:1;

[0056] In step (1), the weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:1; the weight ratio of butyl orthosilicate to active filler is 1:1.8; the weight ratio of reinforcing filler to active filler is 1:1; the weight ratio of active filler to water is 28:100;

[0057] In step (2), the drying condition is 115° C. for 8 hours; the calcination condition is 600° C. for 4 hours;

[0058] The active filler is first-grade fly ash (in accordance with GB / T 1596 standard); the reinforcing filler is a combination of hydrotalcite and oxide whiskers; the weight ratio of hydrotalcite to oxide whiskers is 1:2.6; the hydrotalcite is Kaisma's hydrotalcite, model 1-C, with an average particle size of 0.6 μm; oxide whiskers are A1203 whiskers purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average particle size of 2000 mesh;

[0059] The cement is 52.5 grade ordinary Portland cement;

[0060] Sodium carboxymethyl cellulose is Asahi Kasei cross-linked sodium carboxymethyl cellulose ND-2HS;

[0061] The polymer powder is tetrafluoroethylene-hexafluoropropylene copolymer of the American 3M brand with the grade of 6322PZ, and its average particle size is 25.6 microns;

[0062] The average particle size of quartz sand is 120 mesh;

[0063] The coagulant is a combination of gypsum powder and aluminum sulfate; the weight ratio of gypsum powder to aluminum sulfate is 1:1;

[0064] The water reducer is ST-02A polycarboxylic acid high-performance water reducer;

[0065] The foaming agent is hydrogen peroxide;

[0066] The preparation process of environmentally friendly foamed mortar for wall materials includes: S1 mixing cement, modified composite active filler, sodium carboxymethyl cellulose, polymer powder and quartz sand to obtain a dry mixture; S2 adding a coagulant, a water reducer and water to the dry mixture to obtain a mixture; S3 adding a foaming agent to the mixture and stirring for 5 seconds to obtain the environmentally friendly foamed mortar for wall materials.

[0067] Example 2

[0068] An environmentally friendly foamed mortar for wall materials, which comprises, by weight: 170 parts of cement, 70 parts of modified composite active filler, 0.5 parts of sodium carboxymethyl cellulose, 60 parts of high molecular polymer powder, 20 parts of quartz sand, 3 parts of accelerator, 1 part of water reducer, 7 parts of foaming agent, and 120 parts of water;

[0069] The preparation process of the modified composite active filler comprises: step (1) dispersing butyl orthosilicate, active filler and reinforcing filler in water, adding hexadecyltrimethylammonium bromide and ammonium bicarbonate to mix, then adjusting the pH value to 11.8 with ammonia water (nitrogen content is 26wt%), and finally reacting at 135°C for 32 hours to obtain a mixture; step (2) filtering, solid phase drying and calcining the mixture in sequence to obtain the modified composite active filler;

[0070] In step (1), the weight ratio of butyl orthosilicate to hexadecyltrimethylammonium bromide is 25:1; the weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:1.2; the weight ratio of butyl orthosilicate to active filler is 1:2; the weight ratio of reinforcing filler to active filler is 1:1; the weight ratio of active filler to water is 30:100; in step (2), the drying condition is drying at 120°C for 8 hours; the calcination condition is calcining at 550°C for 4 hours;

[0071] The active filler is first-grade fly ash (in accordance with GB / T 1596 standard); the reinforcing filler is a combination of hydrotalcite and oxide whiskers; the weight ratio of hydrotalcite to oxide whiskers is 1:2.8; the hydrotalcite is Kaisma's hydrotalcite, model 1-C, with an average particle size of 0.6 μm; oxide whiskers are A12O3 whiskers purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average particle size of 2000 mesh;

[0072] The cement is 52.5 grade ordinary Portland cement;

[0073] Sodium carboxymethyl cellulose is Asahi Kasei cross-linked sodium carboxymethyl cellulose ND-2HS;

[0074] The polymer powder is Japanese Daikin brand polytetrafluoroethylene with the grade F-131, and its average particle size is 19.7 microns;

[0075] The average particle size of quartz sand is 120 mesh;

[0076] The coagulant is a combination of gypsum powder and aluminum sulfate; the weight ratio of gypsum powder to aluminum sulfate is 1:1;

[0077] The water reducer is ST-02A polycarboxylic acid high-performance water reducer;

[0078] The foaming agent is hydrogen peroxide;

[0079] The preparation process of environmentally friendly foamed mortar for wall materials includes: S1 mixing cement, modified composite active filler, sodium carboxymethyl cellulose, polymer powder and quartz sand to obtain a dry mixture; S2 adding a coagulant, a water reducer and water to the dry mixture to obtain a mixture; S3 adding a foaming agent to the mixture and stirring for 5 seconds to obtain the environmentally friendly foamed mortar for wall materials.

[0080] Comparative Example 1

[0081] This comparative example provides an environmentally friendly foamed mortar for wall materials, which includes, by weight, 155 parts of cement, 34 parts of active filler, 34 parts of reinforcing filler, 0.38 parts of sodium carboxymethyl cellulose, 38 parts of high molecular polymer powder, 16 parts of quartz sand, 2.5 parts of accelerator, 0.8 parts of water reducer, 6 parts of foaming agent, and 112 parts of water;

[0082] The active filler is first-grade fly ash (in compliance with GB / T 1596 standard);

[0083] The reinforcing filler is a combination of hydrotalcite and oxide whiskers; the weight ratio of hydrotalcite to oxide whiskers is 1:(2.5-2.8); the hydrotalcite is the hydrotalcite of Kaisma, model 1-C, with an average particle size of 0.6 μm; oxide whiskers are A12O3 whiskers purchased from Qinghe Chaotai Metal Materials Co., Ltd., with an average particle size of 2000 mesh;

[0084] The cement is 52.5 grade ordinary Portland cement;

[0085] Sodium carboxymethyl cellulose is Asahi Kasei cross-linked sodium carboxymethyl cellulose ND-2HS;

[0086] The polymer powder is tetrafluoroethylene-hexafluoropropylene copolymer of the American 3M brand with the grade of 6322PZ, and its average particle size is 25.6 microns;

[0087] The average particle size of quartz sand is 120 mesh;

[0088] The coagulant is a combination of gypsum powder and aluminum sulfate; the weight ratio of gypsum powder to aluminum sulfate is 1:1;

[0089] The water reducer is ST-02A polycarboxylic acid high-performance water reducer;

[0090] The foaming agent is hydrogen peroxide;

[0091] The preparation process of environmentally friendly foamed mortar for wall materials includes: S1 mixing cement, active filler, reinforcing filler, sodium carboxymethyl cellulose, polymer powder and quartz sand to obtain a dry mixture; S2 adding a coagulant, a water reducer and water to the dry mixture to obtain a mixture; S3 adding a foaming agent to the mixture and stirring for 5 seconds to obtain the environmentally friendly foamed mortar for wall materials.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 1 is:

[0094] The butyl orthosilicate used in preparing the modified composite active filler is replaced by aluminum hydroxide.

[0095] Comparative Example 3

[0096] The difference between this comparative example and Example 1 is:

[0097] The weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:0.1.

[0098] Comparative Example 4

[0099] The difference between this comparative example and Example 1 is:

[0100] The weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:3.

[0101] Comparative Example 5

[0102] The difference between this comparative example and Example 1 is:

[0103] The reinforcing filler is solely hydrotalcite.

[0104] Comparative Example 6

[0105] The difference between this comparative example and Example 1 is:

[0106] The reinforcing filler is solely Al2O3 whisker;

[0107] Comparative Example 7

[0108] The difference between this comparative example and Example 1 is:

[0109] The modified composite active filler is 106 parts, and the high molecular polymer powder is 0 parts.

[0110] Performance Testing

[0111] The foamed mortars in the embodiment and the comparative example were respectively poured into the pre-prepared molds, and vibrated for 30 seconds with a vibration machine to fully fill the molds with the mortar. After molding, the molds were cured at room temperature (20-27° C.) for 7 days and then demolded to obtain the test samples. The quality of the test samples was recorded and the test samples were tested as follows:

[0112] 1. Thermal insulation: It is measured by thermal conductivity. The smaller the thermal conductivity, the better the thermal insulation. The thermal conductivity test is carried out in accordance with the standard of GB / T 10294-2008.

[0113] 2. Compressive strength test: measured in accordance with GB / T 5486-2008.

[0114] 3. Carry out freeze-thaw cycle test in accordance with the specification "Test Method for Performance of Autoclaved Aerated Concrete" (GB / T 11969-2020), test and record the mass and compressive strength of the test sample after 50 freeze-thaw cycles, and calculate the mass loss rate and compressive strength loss rate.

[0115] The test results are shown in Table 1.

[0116] Table 1 Performance test results

[0117]

[0118] It can be seen from the above performance test results that the foamed mortars in Examples 1-2 have excellent strength, thermal insulation and cyclic frost resistance, especially the comprehensive performance of Example 1 is the most outstanding. It is speculated that this is because the polymer powder, modified composite active filler and other components in the system interact to form a specific network structure, and the modified composite active filler has the ability to improve the workability and fluidity of the slurry, cut off the capillary passage in a freezing environment, and reduce the effect of the capillary. However, the comparative examples did not adopt the necessary technical solutions, resulting in that their corresponding performance tests were significantly worse than those of the embodiments. The active fillers and reinforcing fillers used in comparative example 1 were not modified to form modified composite active fillers, and the strength, thermal insulation and cyclic frost resistance of the final product were significantly reduced, indicating that the modified composite active fillers in the present invention are particularly important for the construction of the foaming system network of the present invention; in comparative example 2, butyl orthosilicate was replaced by aluminum hydroxide, and the strength of the final product was reduced to a certain extent; in comparative example 3, the amount of ammonium bicarbonate was reduced, and the overall performance of the final product was reduced; in comparative example 4, the amount of ammonium bicarbonate was increased, and the overall performance of the final product was reduced, especially the strength and frost resistance. Comparative examples 3-4 prove that carbon Too much or too little ammonium bicarbonate will affect the performance of the final product; in Example 5, the reinforcing filler is hydrotalcite alone, and the performance of the final mortar product is reduced, especially the strength; in Example 6, the reinforcing filler is Al2O3 whisker alone, and the performance of the final mortar product is reduced, especially the strength. Comparative Examples 5-6 prove that the present invention needs to use hydrotalcite and oxide whiskers, especially Al2O3 whiskers, to work together to better increase the overall performance of the foamed mortar product, especially the strength; in Example 7, no polymer powder is added, and the overall performance of the foamed mortar product is reduced, especially the thermal insulation. Comparative Example 7 shows that the addition of polymer powder in the present invention can better increase the thermal insulation of the foamed mortar product. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0119] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An environmentally friendly foamed mortar for wall materials, characterized in that: The environmentally friendly foamed mortar comprises, by weight: 100-200 parts of cement, 40-90 parts of modified composite active filler, 0.1-0.8 parts of sodium carboxymethyl cellulose, 30-50 parts of high molecular polymer powder, 5-30 parts of quartz sand, 1-5 parts of accelerator, 0.5-2 parts of water reducer, 3-10 parts of foaming agent, and 80-150 parts of water; Wherein, the preparation process of the modified composite active filler comprises: Step (1) dispersing butyl orthosilicate, active filler and reinforcing filler in water, adding hexadecyltrimethylammonium bromide and ammonium bicarbonate to mix, then adjusting the pH to 10-12 with ammonia water, and finally reacting in a closed state at 120-150° C. for 24-32 hours to obtain a mixture; Step (2) filtering, solid phase drying and calcining the mixed material in sequence to obtain a modified composite active filler.

2. The environmentally friendly foamed mortar according to claim 1, characterized in that: In step (1): The weight ratio of the butyl orthosilicate to the hexadecyltrimethylammonium bromide is (10-30):1; The weight ratio of hexadecyltrimethylammonium bromide to ammonium bicarbonate is 1:(0.5-2); The weight ratio of the butyl orthosilicate to the active filler is 1:(1-5); The weight ratio of the reinforcing filler to the active filler is 1:(0.6-2); The weight ratio of the active filler to water is (20-40):

100.

3. The environmentally friendly foamed mortar according to claim 1, characterized in that: The drying condition is: drying at 100-120°C for 2-10 hours; the calcining condition is: calcining at 550-650°C for 3-5 hours.

4. The environmentally friendly foamed mortar according to any one of claims 1 to 3, characterized in that: The active filler is fly ash; the reinforcing filler is a combination of hydrotalcite and oxide whiskers.

5. The environmentally friendly foamed mortar according to claim 4, characterized in that: The weight ratio of the hydrotalcite to the oxide whisker is 1:(1-4); the average particle size of the hydrotalcite is 0.1-5 microns; the oxide whisker is selected from Al2O3 whisker, TiO2 whisker and MgO whisker; the average particle size of the oxide whisker is 1800-2600 mesh.

6. The environmentally friendly foamed mortar according to any one of claims 1 to 3, characterized in that: The cement is selected from at least one of ordinary Portland cement, sulphoaluminate cement, composite Portland cement, ferroaluminate cement and high-alumina refractory cement.

7. The environmentally friendly foamed mortar according to any one of claims 1 to 3, characterized in that: The high molecular polymer powder is selected from at least one of polyarylsulfone, tetrafluoroethylene-hexafluoropropylene copolymer, polytetrafluoroethylene, polyimide and polyphenylene sulfide; and the average particle size of the high molecular polymer powder is 15-50 microns.

8. The environmentally friendly foamed mortar according to any one of claims 1 to 3, characterized in that: The coagulant is selected from at least one of gypsum powder, lithium carbonate, sodium silicate, aluminum sulfate, sodium nitrate, calcium nitrate, sodium sulfate and sodium carbonate.

9. The environmentally friendly foamed mortar according to any one of claims 1 to 3, characterized in that: The water reducer is selected from at least one of a naphthalene water reducer, an aliphatic water reducer and a polycarboxylic acid water reducer; and the foaming agent is hydrogen peroxide.

10. A process for preparing the environmentally friendly foamed mortar for wall materials according to any one of claims 1 to 9, characterized in that: The preparation process includes: S1: mixing cement, modified composite active filler, sodium carboxymethyl cellulose, high molecular polymer powder and quartz sand to obtain a dry mix; S2 adds a coagulant, a water reducing agent and water to the dry mix to obtain a mixed material; S3 adds a foaming agent into the mixed material and stirs for 2-10 seconds to obtain an environmentally friendly foamed mortar for wall materials.

Citation Information

Patent Citations

  • Method for preparing mesoporous silicon oxide microspheres

    CN102992329A

  • Heat-preservation sound-proof low-density foamed concrete

    CN105218146A

  • Mesoporous material composite foamed cement and preparation method thereof

    CN111606624A

  • Method for producing composite micro-mesoporous material MTW / WMS with "core-shell" structure

    RU2815641C1